Parenté génétique et correspondances phonétiques. A propos du proto-mondial - Jucquois, Guy (My University, 2001)
Irrespective of the traditional reconstructions related to the theory of well known families of languages, such as Indo-European or Semitic, some researchers have aimed at rebuilding super-families, recently going as far as a Proto-global family. Several puzzling agreements between their proposals and the reconstructions made by the genetics of populations further ascertain their assumptions. These new developments lead us to re-examine various methodological aspects, upheld on the basis of the typical fields of genetic linguistics and more specifically, the necessary connections between the certification of a genetic relationship and the previous establishment of phonetic correspondences.